Development and Validation of Local Context-Based Literacy and Numeracy Instruments for the Sekolah Sepanjang Hari (SSH) Program - Tulalessy, Quin Donspri; Suparman, Achmad Rante; Turirday, Helena Trivona; Yenusi, Kaleb Amaghi (LP. Ma'arif Janggan Magetan, 2026)
This This study aims to develop and validate a basic literacy and numeracy assessment instrument for participants in the Sekolah Sepanjang Hari Program (SSH) in South Sorong Regency, for both regular students and dropouts. The instrument is designed to map Reading, writing, and numeracy skills as the foundation for lifelong learning. Development was carried out through four stages: theoretical construct analysis, expert content validation, field trials, and construct validity analysis using Confirmatory Factor Analysis (CFA). The content validation results showed an average Content Validity Index (CVI) of 0.92, indicating a high fit between the test items and the constructs. A pre-test on 30 students was used to refine the language and local context, while the main pre-test on 145 students ensured proportional levels of readability and difficulty. The CFA results confirmed a three-dimensional structure with perfect model fit (CFI = 1.000; TLI = 1.005; RMSEA = 0.000; SRMR = 0.043; GFI = 0.939). The factor loading values of 0.67–0.92, composite reliability of 0.899–0.918, and AVE of 0.598–0.653 indicate strong validity and reliability. This instrument has been proven feasible and contextually relevant, making it suitable for diagnostic assessment of students’ basic abilities in non-formal education, especially in the 3T regions